Simulation of power extraction from tidal currents by flapping foil hydrokinetic turbines in tandem formation. (September 2015) - Karbasian, H.R.; Esfahani, J.A.; Barati, E.
Abstract: In the present study the power extraction possibility by a number of flapping hydrofoils in tandem formation is investigated. A code is developed to predict power extraction capacity for the various number of flapping hydrofoils based on the kinematic and hydrodynamic models. The selected hydrodynamic model follows two dimensional quasi-steady hydrodynamic instability formulation. It is shown that the power extraction is also possible from water stream with the low Reynolds number. As a result of power extraction at low speed flows, the predicted maximum power efficiency is also in lower flapping frequencies. Furthermore, it is found that there are limited number of required flapping hydrofoils in tandem formation, in which the power influence rate drops notably after the second flapping hydrofoil. The flapping hydrofoils at downstream also experience higher hydrodynamic forces, while the flapping hydrofoil kinematics is the key parameter to harness extracted power. As a result of this investigation, the introduced model and code can be used as one of initial tools to predict power capacity for obtaining vast concept regarding tidal sites with the flapping foil hydrokinetic turbines. Highlights: The power extraction possibility by a number of flapping foils in tandem formation is investigated. A code is developed to predict power extraction capacity for the various number of flapping foils. Notable drop in the power influence rate after the second flapping foil. The higher power efficiency at the low Reynolds number and flapping frequency.